Ipon: Aplikasi Terjemahan Langsung IndonesiaJepang Untuk Membantu Komunikasi Pekerja Magang Indonesia Di Jepang Berbasis Mobile - Abdul, Ahmad; Prawita, Fat'hah Noor (eProceedings of Applied Science, 2024)
From 1993 to 2022, 94,348 workers Indonesian interns (kenshūsei) have been sent to Japan through an apprenticeship program organized by Indonesian government, with 13,699 interns participate in 2022. This program aims to master the knowledge, work ethic and practices in Japan. However, Interns often face challenges in adaptation cultural and language barriers that affect performance and their social interactions. Cultural gaps and barriers language can cause misunderstandings, influence productivity, and hinder effective social interaction between interns and their Japanese coworkers. For To overcome this obstacle, the IPON Live application was developed Translation, designed to facilitate communication real-time two-way between Indonesian interns and Japanese society. This app offers features like live translation, speech-to-text, text-to-speech, menu settings to prevent misunderstandings, level menu courtesy of translation results, and Japanese romaji for makes it easier for workers to communicate without having to read hiragana and katakana. With this application, it is hoped that the Indonesian interns can adapt more easily, communicate, and understand work culture in Japan. This matter will help them maximize their potential and their contributions during the apprenticeship program, as well improve the quality of interaction and collaboration with colleagues Japanese work. The author gets feedback for the application IPON Live Translation can be more useful, and with feedback from sources who implemented the application Testing was carried out again on the sources provide feedback and other sources, authors get the final results according to the Usefulness test data, as many as 89.9% of interviewees Strongly Agree that this application useful in its features. Keyword: Indonesian Internship, Direct Translation, Speech-to-text, Text-to-speech, Politeness level menu, Japanese Romaji, communication barriers